1984
DOI: 10.1093/ajcp/81.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Immune Deficiency Syndrome: Postmortem Findings

Abstract: The autopsies of 13 male homosexuals with acquired immune deficiency syndrome (AIDS) were reviewed. All patients had laboratory evidence of cellular immune dysfunction. The most common diagnoses made were disseminated cytomegalovirus infection in 12 patients and Kaposi's sarcoma in 10. All patients infected with cytomegalovirus had pulmonary compromise. The adrenal glands and gastrointestinal tract also were involved often by cytomegalovirus. Cytomegalovirus infection of organs uncommonly affected such as hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(30 citation statements)
references
References 0 publications
2
27
0
1
Order By: Relevance
“…Fourteen of these patients had chronic renal failure and FSGS was seen in only 43% (6) of these patients on renal biopsy [13]. Similarly some autopsy studies have also found HIVAN as an uncommon lesion on examination of renal tissue [14][15][16][17][18][19][20]. Lower proportion of AfricanAmericans in many of these studies could have accounted for low prevalence of HIVAN.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen of these patients had chronic renal failure and FSGS was seen in only 43% (6) of these patients on renal biopsy [13]. Similarly some autopsy studies have also found HIVAN as an uncommon lesion on examination of renal tissue [14][15][16][17][18][19][20]. Lower proportion of AfricanAmericans in many of these studies could have accounted for low prevalence of HIVAN.…”
Section: Discussionmentioning
confidence: 99%
“…Following these, the next most frequent tumors were lymphoid neoplasias and KS (2.7% and 2.3%, respectively). There are studies showing greater prevalence of lymphoid tumors 7,12,20,27 and others presenting greater frequency of KS 1,19,24,28 among HIV-positive patients. In our study, these frequencies were similar, as shown by other authors 23,32 .…”
mentioning
confidence: 99%
“…Other investigators have associated cerebral infarcts in HIV-infected patients with hepatitis B 42 (hepatitis B or C serology was positive in 6 of our patients), as well as with a prothrombotic state related to protein S deficiency, 35,36 antiphospholipid antibodies, 39,40 or disseminated intravascular coagulopathy. 4,11,12 We have protein S levels, which were normal, for only 1 patient, and none of our patients had antiphospholipid antibodies measured. Thus, the theoretical possibility of "hypercoagulability" remains, although intravascular thrombi, recent or organized, were seen only rarely in this and other autopsy series, even in those cases with very recent infarcts.…”
Section: Discussionmentioning
confidence: 66%